Silica sol combined cement-free castable for tapping channel and preparation method of silica sol combined cement-free castable

By using cementless castable material combined with silicon sol in blast furnace discharge groove application, the problem of poor construction performance in the prior art is solved, and the effect of significantly improving mechanical and high-temperature performance is achieved, and the service life of the material is extended.

CN119683977APending Publication Date: 2025-03-25YIXING REFRACTORY EQUIP & MATERIAL FACTORY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411892539.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing silicon sol-bound castables have poor construction performance in blast furnace iron discharge groove applications, which limits their application scope.

Method used

40~61 wt.% bauxite, 8~12 wt.% white corundum, 14~20 wt.% silicon carbide, 8~13 wt.% dense corundum, 5~8 wt.% α-alumina fine powder and 2~5 wt.% ball asphalt were used as raw materials, plus 0.1~0.4 wt.% magnesium sand, 0.2~0.6 wt.% metal silicon, 0.05~0.2 wt.% water reducer and 5.5~7.5 wt.% silicon sol were used to obtain a cementless castable for the iron discharge groove bound by dry mixing.

Benefits of technology

It significantly improves the mechanical properties and high-temperature properties of cementless castables for iron drainage grooves, improves construction performance and thermal shock stability, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a silica sol combined cement-free castable for an iron runner and a preparation method of the silica sol combined cement-free castable, and belongs to the technical field of refractory materials. The preparation method comprises the following steps: taking 40 to 61 weight percent of bauxite, 8 to 12 weight percent of white corundum, 14 to 20 weight percent of silicon carbide, 8 to 13 weight percent of compact corundum, 5 to 8 weight percent of alpha-aluminum oxide micro powder and 2 to 5 weight percent of ball pitch as raw materials, additionally adding 0.1 to 0.4 weight percent of magnesia, 0.2 to 0.6 weight percent of metal silicon, 0.05 to 0.2 weight percent of water reducing agent and 5.5 to 7.5 weight percent of silica sol, and uniformly dry-mixing to prepare the silica sol combined cement-free castable for the tapping channel. According to the prepared cement-free castable, the problems that silica sol combined castable is poor in construction performance and low in demolding strength are effectively solved, and the mechanical performance and the high-temperature performance of the castable for the tapping channel are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a silica sol-bonded cement-free castable for an iron ditch and a preparation method thereof. Background Art

[0002] The blast furnace taphole is an indispensable part of the steel smelting process. It is responsible for guiding the molten iron from the blast furnace taphole to the molten iron ladle, ensuring the smooth discharge of the molten iron and the continuity of production. The life of the taphole directly affects the normal production and work efficiency of the blast furnace.

[0003] The binder used in general refractory castables is calcium aluminate cement. Traditional calcium aluminate cement contains Ca 2+ 、Na + Plasma produces low melting point phases of calcite and anorthite at high temperatures, which are not conducive to the high temperature performance of castables and affect the performance and life of materials. Silica sol is a solution formed by silica colloidal particles dispersed in water. In comparison, castables combined with silica sol have obvious advantages over cement-bonded castable refractory materials in terms of drying performance, baking performance, sintering performance, volume stability and high temperature strength, and have gradually attracted the attention of scientific researchers and have been put into practical application in castables.

[0004] The low demoulding strength and poor construction performance of silica sol-bonded castables limit their application in the field of refractory materials for blast furnace iron-making plants. Summary of the invention

[0005] In view of the above problems existing in the prior art, the technical problem to be solved by the present invention is to provide a silica sol-bonded cement-free castable for an iron outlet ditch, which has high mechanical properties and stability; another technical problem to be solved by the present invention is to provide a preparation method of a silica sol-bonded cement-free castable for an iron outlet ditch.

[0006] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0007] A preparation method of a silica sol-bonded cement-free castable for an iron tapping ditch comprises the following steps: using 40-61 wt.% of bauxite, 8-12 wt.% of white corundum, 14-20 wt.% of silicon carbide, 8-13 wt.% of dense corundum, 5-8 wt.% of alpha-alumina micropowder and 2-5 wt.% of spherical asphalt as raw materials, adding 0.1-0.4 wt.% of magnesia, 0.2-0.6 wt.% of metallic silicon, 0.05-0.2 wt.% of a water reducing agent and 5.5-7.5 wt.% of silica sol as raw materials, dry-mixing the raw materials uniformly, and preparing the silica sol-bonded cement-free castable for an iron tapping ditch.

[0008] Preferably, the method for preparing the silica sol-bonded cement-free castable for the iron outlet ditch uses 50 wt.% of bauxite, 10 wt.% of white corundum, 18 wt.% of silicon carbide, 11 wt.% of dense corundum, 6 wt.% of α-alumina powder and 3 wt.% of spherical asphalt as raw materials, and adds 0.3 wt.% of magnesia, 0.5 wt.% of metallic silicon, 0.075 wt.% of water reducer and 6.7 wt.% of silica sol to the raw materials, and dry-mixes them evenly to obtain the silica sol-bonded cement-free castable for the iron outlet ditch.

[0009] Preferably, the Al2O3 content of the bauxite is ≥86wt.%, and the particle gradation of the bauxite is: the mass ratio of bauxite with a particle size of 1-3mm, bauxite with a particle size of 3-5mm and bauxite with a particle size of 5-8mm is 3:2:4.

[0010] Preferably, the Al2O3 content of the white corundum is ≥99wt.%, and the particle size is ≤1mm.

[0011] Preferably, the SiC content of the silicon carbide is ≥97wt.%, and the particle gradation of the silicon carbide is: the mass ratio of silicon carbide with a particle size of ≤325 mesh to silicon carbide with a particle size of 0-1 mm is 1:1.

[0012] Preferably, the water reducer is sodium hexametaphosphate or polycarboxylate water reducer FS20.

[0013] Preferably, the solid content of the silica sol is 30 wt.%.

[0014] Preferably, the Al2O3 content of the dense corundum is ≥98wt.%, and the particle size is ≤325 mesh; the Al2O3 content of the α-alumina micropowder is ≥99wt.%, and D50=0.7 μm.

[0015] Preferably, the MgO content of the magnesia is ≥96 wt.%, and the particle size is ≤325 mesh.

[0016] The preparation method can prepare silica sol-bonded cement-free castable for iron outlet channel.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The cement-free castable for the iron ditch of the present invention uses silica sol to replace the calcium aluminate cement in the traditional castable. The traditional calcium aluminate cement contains Ca 2+ 、Na + Plasma produces low melting point phases of calcite and anorthite at high temperatures, which are not conducive to the high temperature performance of the castable and affect the performance and life of the material. The mechanical properties of cement-free iron ditch castables combined with silica sol are significantly improved in high temperature performance;

[0019] (2) The present invention adds magnesia as a coagulant. After magnesia is added to the silica sol and combined with the cement-free castable, a hydration reaction occurs, causing the Si-OH on the surface of the SiO2 particles in the silica sol to break to form Si-O broken bonds. Thereafter, Mg 2+ Ion bonds the Si-O broken bonds on the surface of silica sol particles, and then combines the SiO2 sol particles together to form a three-dimensional network structure, which promotes the coagulation and hardening of the castable;

[0020] (3) The magnesia added in the present invention can react chemically with alumina (Al2O3) and other components in the iron ditch castable to generate a magnesia-alumina spinel (MgAl2O4) compound. The Kirkendall effect exists in the MgAl2O4 generation process, and micro voids are generated while the spinel is generated. These micro voids absorb and disperse thermal stress during the use of the castable, thereby increasing the thermal shock stability of the castable. At the same time, the addition of magnesia generates magnesia-alumina spinel, which increases the slag resistance of the castable. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described below in conjunction with specific embodiments. In the following embodiments, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.

[0022] The specific specifications of the raw materials used in the following examples are as follows:

[0023] The Al2O3 content of bauxite is ≥86wt.%, and the particle gradation of bauxite is: the mass ratio of bauxite with a particle size of 1~3mm, bauxite with a particle size of 3~5mm and bauxite with a particle size of 5~8mm is 3:2:4.

[0024] The Al2O3 content of white corundum is ≥99wt.%, and the particle size is ≤1mm.

[0025] The SiC content of silicon carbide is ≥97wt.%, and the particle gradation of silicon carbide is: the mass ratio of silicon carbide with a particle size of ≤325 mesh to silicon carbide with a particle size of 0-1 mm is 1:1.

[0026] The water reducer is sodium hexametaphosphate or polycarboxylate water reducer FS20, and FS20 is FS20 polymer water reducer produced by BASF of Germany.

[0027] The solid content of the silica sol is 30 wt.%.

[0028] The Al2O3 content of dense corundum is ≥98wt.%, and the particle size is ≤325 mesh; the Al2O3 content of α-alumina micropowder is ≥99wt.%, and D50=0.7 μm.

[0029] The MgO content of magnesia is ≥96 wt.%, and the particle size is ≤325 mesh.

[0030] The fixed C content of ball asphalt is ≥60% and the particle size is ≤1mm.

[0031] The Si content of the metallic silicon is ≥98wt.%, and the particle size is ≤400 mesh.

[0032] The calcium aluminate cement is Secar 71, with an Al2O3 content of ≥68.5wt.%, and a CaO content of ≤31 wt.%.

[0033] The SiO2 content in the silicon micropowder is greater than 95wt.%, and the particle size D50 is equal to 0.15μm.

[0034] Example 1

[0035] A method for preparing a silica sol-bonded cement-free castable for an iron ditch comprises the following steps:

[0036] 1) Weigh the formula according to the ratio:

[0037] 50 wt.% of bauxite, 10 wt.% of white corundum, 18 wt.% of silicon carbide, 11 wt.% of dense corundum, 6 wt.% of α-alumina powder and 3 wt.% of ball pitch are used as raw materials, and 0.3 wt.% of magnesia, 0.5 wt.% of metallic silicon, 0.075 wt.% of sodium hexametaphosphate and 6.7 wt.% of silica sol are added as raw materials;

[0038] 2) Bauxite, white corundum, silicon carbide, dense corundum, α-alumina powder, spherical asphalt, magnesia, metallic silicon and sodium hexametaphosphate are mixed evenly in a mixer, and then silica sol is added for stirring; after stirring evenly, the stirred castable is poured into a mold, and cast on a vibration table to obtain a test bar; then the sample is demolded, cured, dried and heat-treated to obtain a cement-free castable for an iron ditch combined with silica sol.

[0039] Example 2

[0040] A method for preparing a silica sol-bonded cement-free castable for an iron ditch comprises the following steps:

[0041] 1) Weigh the formula according to the ratio:

[0042] 50 wt.% of bauxite, 10 wt.% of white corundum, 18 wt.% of silicon carbide, 11 wt.% of dense corundum, 6 wt.% of α-alumina powder and 3 wt.% of ball pitch are used as raw materials, and 0.1 wt.% of magnesia, 0.5 wt.% of metallic silicon, 0.075 wt.% of sodium hexametaphosphate and 6.7 wt.% of silica sol are added as raw materials;

[0043] 2) Bauxite, white corundum, silicon carbide, dense corundum, α-alumina powder, spherical asphalt, magnesia, metallic silicon and sodium hexametaphosphate are mixed evenly in a mixer, and then silica sol is added for stirring; after stirring evenly, the stirred castable is poured into a mold, and cast on a vibration table to obtain a test bar; then the sample is demolded, cured, dried and heat-treated to obtain a cement-free castable for an iron ditch combined with silica sol.

[0044] Example 3

[0045] A method for preparing a silica sol-bonded cement-free castable for an iron ditch comprises the following steps:

[0046] 1) Weigh the formula according to the ratio:

[0047] 50 wt.% bauxite, 10 wt.% white corundum, 18 wt.% silicon carbide, 11 wt.% dense corundum, 6 wt.% α-alumina powder and 3 wt.% ball pitch are used as raw materials, and 0.3 wt.% magnesia, 0.5 wt.% metallic silicon, 0.075 wt.% FS20 and 6.7 wt.% silica sol are added as raw materials;

[0048] 2) Bauxite, white corundum, silicon carbide, dense corundum, α-alumina powder, spherical asphalt, magnesia, metallic silicon and sodium hexametaphosphate are mixed evenly in a mixer, and then silica sol is added for stirring; after stirring evenly, the stirred castable is poured into a mold, and cast on a vibration table to obtain a test bar; then the sample is demolded, cured, dried and heat-treated to obtain a cement-free castable for an iron ditch combined with silica sol.

[0049] Example 4

[0050] A method for preparing a silica sol-bonded cement-free castable for an iron ditch comprises the following steps:

[0051] 1) Weigh the formula according to the ratio:

[0052] 50 wt.% of bauxite, 10 wt.% of white corundum, 18 wt.% of silicon carbide, 11 wt.% of dense corundum, 6 wt.% of α-alumina powder and 3 wt.% of ball pitch are used as raw materials, and 0.3 wt.% of magnesia, 0.5 wt.% of metallic silicon, 0.1 wt.% of sodium hexametaphosphate and 6.7 wt.% of silica sol are added as raw materials;

[0053] 2) Bauxite, white corundum, silicon carbide, dense corundum, α-alumina powder, spherical asphalt, magnesia, metallic silicon and sodium hexametaphosphate are mixed evenly in a mixer, and then silica sol is added for stirring; after stirring evenly, the stirred castable is poured into a mold, and cast on a vibration table to obtain a test bar; then the sample is demolded, cured, dried and heat-treated to obtain a cement-free castable for an iron ditch combined with silica sol.

[0054] Comparative Example 1

[0055] The process of preparing cement castable for iron ditch is as follows: 50 wt.% of bauxite, 10 wt.% of white corundum, 18 wt.% of silicon carbide, 11 wt.% of dense corundum, 6 wt.% of α-alumina powder and 3 wt.% of spherical asphalt are used as raw materials, and 0.5 wt.% of metallic silicon, 0.1 wt.% of sodium hexametaphosphate, 2 wt.% of silicon powder, 3 wt.% of calcium aluminate cement and 4.7 wt.% of water are added; bauxite, white corundum, silicon carbide, dense corundum, α-alumina powder, spherical asphalt, metallic silicon, calcium aluminate cement, silicon powder and sodium hexametaphosphate are mixed evenly by a mixer, and then water is added for stirring; after stirring evenly, the stirred castable is poured into a mold, and cast on a vibration table to obtain a test strip; then the sample is demolded, cured, dried and heat treated.

[0056] The castables prepared in Examples 1 to 4 and Comparative Example 1 were subjected to performance tests, and the results are shown in Table 1. o The castable sample after sintering at C × 3 h was placed in 1100 o The samples were kept in a high-temperature electric furnace at 1500℃ for 30 min, then taken out and water-cooled for 5 min, and the cycle was repeated 5 times. The thermal shock flexural strength retention rate is the ratio of the flexural strength of the sample after thermal shock to the flexural strength of the sample after sintering at 1500℃ for 3h; the slag erosion index is the ratio of the slag erosion area of ​​the crucible hole to the initial area of ​​the crucible hole in the cross section of the static slag resistance sample. The larger the ratio, the more serious the slag erosion.

[0057] Table 1 Performance indexes of castables prepared in Examples 1 to 4 and Comparative Example 1

[0058]

[0059] As can be seen from Table 1, the waterless castable for the iron ditch combined with silica sol in the present invention has good construction performance, and the room-temperature flexural strength of the sample after medium-temperature treatment is increased by more than 35% compared with the cement castable, and the compressive strength is increased by more than 65%; the room-temperature flexural strength of the sample after high-temperature treatment is increased by more than 6% compared with the cement castable, and the compressive strength is increased by more than 30%; the thermal shock stability and slag erosion resistance are also improved.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a silica sol-bonded cement-free castable for an iron ditch, characterized in that: 40-61 wt.% of bauxite, 8-12 wt.% of white corundum, 14-20 wt.% of silicon carbide, 8-13 wt.% of dense corundum, 5-8 wt.% of α-alumina powder and 2-5 wt.% of ball pitch are used as raw materials, and 0.1-0.4 wt.% of magnesia, 0.2-0.6 wt.% of metallic silicon, 0.05-0.2 wt.% of water reducer and 5.5-7.5 wt.% of silica sol are added to the raw materials, and dry-mixed uniformly to prepare a silica sol-bonded cement-free castable for an iron ditch.

2. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: 50 wt.% of bauxite, 10 wt.% of white corundum, 18 wt.% of silicon carbide, 11 wt.% of dense corundum, 6 wt.% of α-alumina powder and 3 wt.% of spherical pitch are used as raw materials, and 0.3 wt.% of magnesia, 0.5 wt.% of metallic silicon, 0.075 wt.% of water reducer and 6.7 wt.% of silica sol are added to the raw materials and dry-mixed uniformly to obtain a silica sol-bonded cement-free castable for an iron ditch.

3. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: The Al2O3 content of the bauxite is ≥86wt.%, and the particle size distribution of the bauxite is: the mass ratio of bauxite with a particle size of 1-3mm, bauxite with a particle size of 3-5mm and bauxite with a particle size of 5-8mm is 3:2:

4.

4. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: The Al2O3 content of the white corundum is ≥99wt.%, and the particle size is ≤1mm.

5. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: The SiC content of the silicon carbide is ≥97wt.%, and the particle gradation of the silicon carbide is: the mass ratio of silicon carbide with a particle size of ≤325 mesh to silicon carbide with a particle size of 0-1 mm is 1:

1.

6. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: The water reducer is sodium hexametaphosphate or polycarboxylate water reducer FS20.

7. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: The solid content of the silica sol is 30 wt.%.

8. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: The Al2O3 content of the dense corundum is ≥98wt.%, and the particle size is ≤325 mesh; the Al2O3 content of the α-alumina micropowder is ≥99wt.%, and D50=0.7 μm.

9. The method for preparing the cement-free castable for the iron ditch combined with silica sol according to claim 1, characterized in that: The magnesia has a MgO content of ≥96 wt.%, and a particle size of ≤325 meshes.

10. The preparation method according to any one of claims 1 to 9 is used to prepare a silica sol-bonded cement-free castable for an iron ditch.